Integrating the dual-system theory in motor: dynamic framework construction for motor decision-making - Huang, Zidong; Wei, Xiaozhuo; Liu, Xutao; Yang, Yechen (Frontiers in Psychology, 2026)
IntroductionExisting research on motor decision-making from a dual-system perspective is often limited by static and dichotomous approaches, failing to fully explain the dynamic fluctuations in decision performance in real sports contexts. Most studies focus on isolated factors, lacking a systematic integration of the interactive effects among external tasks, internal states, and experience levels. Therefore, this study aims to construct a theoretical framework that integrates these three dimensions to reveal the dynamic interaction mechanisms of the dual systems in motor decision-making.MethodsBased on a comprehensive literature review and critical analysis, this theoretical article proposes a framework centered on three core dimensions:task constraints (time pressure, task complexity), physiological states (fatigue, arousal), and experience level (expert-novice paradigm). It further clarifies the specific pathways through which these dimensions influence the dual-system interaction by modulating cognitive resources.ResultsThe study yields a coherent theoretical framework that systematically outlines how the three dimensions interact to influence the dynamic interaction of dual systems. This framework provides a mechanistic explanation for phenomena such as athletes’ performance fluctuations and decision-making errors, confirming the proposed integrative perspective.DiscussionThe proposed framework not only offers a more systematic and ecologically valid explanatory model for the field of motor decision-making but also, as the theoretical foundation for a series of subsequent studies, provides top-level design and methodological guidance for future empirical research. It promotes a shift from isolated factor analysis to a multi-dimensional interactive view, opening perspectives for exploring complex decision-making mechanisms in real-world sports environments.